Share of food group expenditure in Mexican households according to the gender of the head of household and size of the locality - Jocelyn Jaen; Sonia Collado-López; Brianda Ioanna Armenta-Guirado; Armando G.-Olvera; Mauricio Hernández-F (Cambridge University Press, 2024)
Abstract Objective: To evaluate differences in the percentage of expenditure on food groups in Mexican households according to the gender of the household head and the size of the locality. Design: Analysis of secondary data from the National Household Income and Expenditure Survey (ENIGH) 2018. We estimated the percentage of expenditure on fifteen food groups according to the gender of the head of household and locality size and evaluated the differences using a two-part model approach. Setting: Mexico, 2018. Participants: A nationally representative sample of 74 647 Mexican households. Results: Female-headed households allocated a lower share of expenditure to the purchase of sweetened beverages and alcoholic beverages and higher percentages to milk and dairy, fruits and water. In comparison with metropolitan households, households in rural and urban localities spent more on cereals and tubers, sugar and honey, oil and fat and less on food away from home. Conclusions: Households allocate different percentages of expenditure to diverse food groups according to the gender of the head of the household and the size of the locality where they are located. Future research should focus on understanding the economic and social disparities related to differences in food expenditure, including the gender perspective.